2011
DOI: 10.1021/je101192x
|View full text |Cite
|
Sign up to set email alerts
|

Density, Viscosity, and Surface Tension of Aqueous Solutions of Potassium Glycinate + Piperazine in the Range of (288.15 to 323.15) K

Abstract: Densities and viscosities of aqueous solutions of potassium glycinate (PG) þ piperazine (PZ) composed of x PG /x PZ (mol/mol) = 1.0/0, 0.9/0.1, 0.8/0.2, 0.7/0.3, and 0.6/0.4 have been measured at (288.15, 303.15, 313.15, and 323.15) K. Surface tensions of aqueous solutions of (PG þ PZ) have been determined at 288.15 K. Correlations by means of mathematical fitting were developed for the predictions of density, viscosity, and surface tension of the aqueous solutions of (PG þ PZ) using the experimental data of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
(26 reference statements)
4
28
2
Order By: Relevance
“…Validation details can be also found in our previous work [30,31]. Results of validation in this work using glycol and glycerol at 295.15 K are shown in Table 2.…”
Section: Validation For the Methods And Procedures Of Measurementsmentioning
confidence: 89%
See 2 more Smart Citations
“…Validation details can be also found in our previous work [30,31]. Results of validation in this work using glycol and glycerol at 295.15 K are shown in Table 2.…”
Section: Validation For the Methods And Procedures Of Measurementsmentioning
confidence: 89%
“…Reported results are the average values of five samples. Experiments were carried out by the following procedures [30,31]. (1) Determining the volume of the pycnometer: first, determine the mass of the empty dry pycnometer.…”
Section: Density Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that, as expected, the viscosities of the aqueous PC solutions decrease with the increase of temperature, and increase as the molar concentration of aqueous PC solution increases. Compared with aqueous amino acid salt such as potassium glycinate and potassium taurate, the viscosities of aqueous potassium citrate are larger than that of aqueous potassium glycinate and potassium taurate under the same conditions of concentration and temperature [12,14]. This is because of molecular weight of the potassium citrate is higher than that of them.…”
Section: Viscosity Measurementsmentioning
confidence: 96%
“…The density, viscosity and surface tension of aqueous amino acid salts can also be obtained from the literature [12][13][14] Then the solution was transferred into a 50 mL standard flask and deionized water was added into the flask to the mark. The potassium citrate solution was prepared in a 50 mL standard flask to a given concentration.…”
Section: Introductionmentioning
confidence: 99%